Superiority of diagnostic musculoskeletal ultrasonography compared to clinical examination in detecting subacromial bursitis - Nadim Kamal, M.; Shakoor, M. A.; Chowdhury, Ziaur Rahman; Azad, Abul Kalam; Rahman, Nadia; Islam, Mohammad Asraful (International Journal of Research in Medical Sciences, 2024)
Background: This study compares the diagnostic efficacy of clinical examination and musculoskeletal (MSK) ultrasonography in detecting subacromial bursitis, highlighting their sensitivity, specificity and reliability. Subacromial bursitis is a common cause of shoulder pain. Methods: This cross-sectional comparative study was conducted in the Department of Physical Medicine and Rehabilitation at Bangabandhu Sheikh Mujib Medical University, Dhaka, from January 1, 2024 to June 30, 2024. A total of 80 patients with suspected subacromial bursitis were evaluated, divided into two groups: clinical examination (n=40) and MSK ultrasonography (n=40). Results: MSK ultrasonography demonstrated superior diagnostic performance with a sensitivity of 91.5% and specificity of 89%, compared to clinical examination, which showed sensitivity and specificity values of 63.2% and 57.5% respectively. The interobserver reliability measured by the Kappa Coefficient was significantly higher for MSK ultrasonography (0.88) than for clinical examination (0.50) underscoring the consistency of ultrasound imaging. MSK ultrasonography also detected specific pathological features such as bursal thickening and effusion more effectively. Conclusions: The study emphasizes the need for improved access to MSK ultrasonography in clinical settings, especially in resource-limited areas like Bangladesh, where clinical examination is still the primary diagnostic method despite its limitations. The integration of MSK ultrasonography into routine practice could enhance diagnostic accuracy, reduce misdiagnoses and improve patient outcomes. These findings support the global trend towards imaging-based diagnostics for musculoskeletal conditions, advocating for strategic investments in diagnostic infrastructure and training to bridge the gap in healthcare delivery.